2019
DOI: 10.1111/bju.14853
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric magnetic resonance imaging and follow‐up to avoid prostate biopsy in 4259 men

Abstract: Objective To determine the proportion of men avoiding biopsy because of negative multiparametric magnetic resonance imaging (mpMRI) findings in a prostate MRI expert centre, and to assess the number of clinically significant prostate cancers (csPCa) detected during follow‐up. Patients and methods Retrospective study of 4259 consecutive men having mpMRI of the prostate between January 2012 and December 2017, with either a history of previous negative transrectal ultrasonography‐guided biopsy or biopsy naïve. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 27 publications
0
22
0
1
Order By: Relevance
“…Panebianco V et al showed that csPCa diagnosis free survival (DFS) was 95% after 2 years follow-up [24]. Furthermore, a recent analysis from another cohort largely corroborate this finding by reporting a csPCa DFS of 99.6% after 3 years [25]. In terms of the ProScreen trial this is reassuring as screen positive men (PSA > 3 and 4 K > 7.5%) with a nMRI or negative targeted biopsy are rescreened after 2 years.…”
Section: Discussionmentioning
confidence: 92%
“…Panebianco V et al showed that csPCa diagnosis free survival (DFS) was 95% after 2 years follow-up [24]. Furthermore, a recent analysis from another cohort largely corroborate this finding by reporting a csPCa DFS of 99.6% after 3 years [25]. In terms of the ProScreen trial this is reassuring as screen positive men (PSA > 3 and 4 K > 7.5%) with a nMRI or negative targeted biopsy are rescreened after 2 years.…”
Section: Discussionmentioning
confidence: 92%
“…In this journal, Venderink et al. suggest that more than half the men being investigated for suspected prostate cancer could indeed safely avoid an initial biopsy. However, like other investigators in this field, the authors make an assumption in their study that there is such a paucity of clinically significant cancer in men with PI‐RADS 1 and 2 lesions, that biopsy is not deemed necessary, as in the PRECISION study .…”
mentioning
confidence: 99%
“…In keeping with our continued theme of the highest quality, clinically relevant papers, in this issue of the BJUI we present two MRI-based prostate cancer papers, showing that while we could avoid biopsies in many men without missing significant disease [5], in African-American men on active monitoring, the cancers can be upgraded more frequently and careful follow-up is thus warranted [6].…”
mentioning
confidence: 64%